WHAT KINDS OF COMPETENCES DO WE REQUIRE AT THE EMPLOYMENT MARKET? JOB ADVERTISEMENTS REVIEW BASED ON COLLECTED DATA FROM WORKLINE.HU JOB-SEEKING SITE - Barbara, Pirohov-Tóth (Applied Studies in Agribusiness and Commerce, 2023)
The epidemic of coronavirus induced radical changes on the employment market as well, hence we may reasonably ask what (new) competences do we have to own to become successful in seeking jobs. The goal of this research is to shed light on the employment market’s new competence demands by analysing job offers found on the website workline.hu. Execution of the investigation took place during the Spring of 2022, during which 410 job vacancies were examined. By utilizing the method of content-analysis, the most important competences were defined first, and then, using KSH’s employment rate statistics, crosstab analysis have revelaed the developments of the most paramount key competences, specializations, competence expectations and connections between the regions. Ultimately, I have determined the foreign language knowledge demanded by employers, and other requirements displayed in the advertisements. Based on the results, the most important key competences include precision, independent working skills and excellent communication skills, which fulfilled a major role in sortments both by regions or national economy sectors. Furthermore, the higher skill demands of inviting applications originated from Transdanubial regions were also corroborated. Beyond said competences, however, numerous other factors (consisting but not limited to: computer science knowledge, B-category driver’s license) may also play a significant role during selection of employees. That being said, the examination did not confirm bigger successfulness rate amongst people with foreign language knowledge. Further investigation of the study includes compare and contrast or results with the competence demands found on other job advertisement portals.